Open Educational Resources and Cost Savings Efforts: Lessons from WOU - Arumugam, Prakash V. (International Journal on Open and Distance e-Learning, 2016)
As is the case with many open universities, Wawasan Open University relies on course development of custom-designed course materials with self-instructional properties using commissioned writers. These course materials are usually developed as adaption of textbooks or licensed course materials from other institutions. This eventually took a toll on the finances of the university as it was becoming costly to develop course materials using this model. As it is, proponents of open educational resources (OER) claim that significant cost savings are possible when OER replaces traditional course development collaterals. With the increasing costs of content creation, there was a need to re-evaluate the course development model that WOU employs as well as define a more prudent financial management approach in dealing with escalating costs of course material development and delivery. In the last four years, attempts were made to replace textbooks and licensed coursewares with OER in the course development process to minimise the cost of the development of course materials and make them more accessible to all. There were obvious challenges as the acceptance among academics were low in the use of OER for course development or revision purposes. This paper is an account of the experiences of the School of Business and Administration in their efforts to re-develop (revise) all the courses, on offer, by using OER. There were two significant contributions of this effort; a refinement of the course development model used in the university as well as the tremendous savings in the cost of course development. This little project saved the university a total of RM1.4 million (approximately US$350000) by mid-2016.